Principles of Lending Business Capital for Private Companies - Cut Ayu Erja Nabillah A. Beh; Rio Nugroho Fahmi; Rachmanda Yanuar Pradana; Carolina Septiani (Budapest International Research and Critics University, 2022)
The research, entitled